A Novel RPWN Selective Harmonic Elimination Method for Single-Phase Inverter - Li, Guohua; Liu, Chunwu; Fu, Zhenfang; Wang, Yufeng (Electronics (Basel), 2020)
In the existing random pule width modulation (RPWM) selective harmonic elimination methods, the formula of switching cycle TN+1 is complex, and the duty ratio DN+1 of the next switching cycle needs to be calculated in advance. However, in the case of unknown TN+1, DN+1 is also difficult to calculate accurately, and the two parameters are based on each other. A novel selective harmonic elimination method in RPWM is proposed in this paper. The PWM voltage pulse is placed at the back of the switch cycle, which simplifies the formula of the switch cycle TN+1 and eliminates the need to calculate the duty ratio DN+1. Two kinds of RPWM selective harmonic elimination ideas are summarized. The general formulas of the switch cycle, the effective random number k, and the upper and lower limits of switch frequency corresponding to k are derived. The spectrum shaping of inverter output voltage can be realized without using digital filter in this method. Simple algorithm, small calculation and easy implementation are characteristics of the proposed method. The simulation and experimental results confirm the ability of the proposed method for reducing harmonics at the specific frequency in power spectral density (PSD).